Bahasa Inggris - Ainindya, Diva Galeh; Muazulfa, Tsalatsun Ikhwa (Universitas Veteran Bangun Nusantara, 2023)
Plants play an important role in producing organic substances and oxygen needed by other living things, but plants can potentially threaten and disrupt the diversity of other plants, causing the quality of biodiversity to decline. Plants that develop in Indonesia can come from various parts of the world, and then these foreign plants can become invasive and have a negative impact on the ecosystem. The aim of this research is to determine the potential level of threat from invasive alien species to tree regeneration in Laweyan Village and the impact of invasive alien species on the environment. The method used is sampling using satellite imagery to determine observation points and methods purposive sampling by making a 10×10 m plot. The results obtained were four plant species that were classified as invasive foreign plants in Laweyan Village, namely Leucaena leucocephala, Cnidoscolus aconitifolius, Sandoricum koetjape, Bougainvillea glabra with different levels of risk. The highest risk category is Leucaena leucocephala with a risk index of 115.2, and the second highest is Bougainvillea glabra with a risk index of 112.8. The risk level is medium, namely Cnidoscolus aconitifolius with a risk index of 100.8 and Sandoricum koetjape with a risk index of 56.28.